Canonical singularities on moduli spaces of rational curves via the circle method - Glas, Jakob (arXiv)
By developing a suitable version of the circle method, we show that the space of degree e rational curves on a smooth hypersurface of degree d has only canonical singularities provided its dimension is sufficiently large with respect to e and d.

Presynaptic cAMP-PKA-mediated potentiation induces reconfiguration of synaptic vesicle pools and channel-vesicle coupling at hippocampal mossy fiber boutons - Kim, Olena
It is widely believed that information storage in neuronal circuits involves nanoscopic structural changes at synapses, resulting in the formation of synaptic engrams. However, direct evidence for this hypothesis is lacking. To test this conjecture, we combined chemical potentiation, functional analysis by paired pre-postsynaptic recordings, and structural analysis by electron microscopy (EM) and freeze-fracture replica labeling (FRL) at the murine hippocampal mossy fiber synapse, a key synapse in the trisynaptic circuit of the hippocampus. Biophysical analysis of synaptic transmission revealed that forskolin-induced chemical potentiation increased the readily releasable vesicle pool size and vesicular release probability by 146% and 49%, respectively. Structural analysis of mossy fiber synapses by EM and FRL demonstrated an increase in the number of vesicles close to the plasma membrane and the number of clusters of the priming protein Munc13-1, indicating an increase in the number of both docked and primed vesicles. Furthermore, FRL analysis revealed a significant reduction of the distance between Munc13-1 and CaV2.1 Ca2+ channels, suggesting reconfiguration of the channel-vesicle coupling nanotopography. Our results indicate that presynaptic plasticity is associated with structural reorganization of active zones. We propose that changes in potential nanoscopic organization at synaptic vesicle release sites may be correlates of learning and memory at a plastic central synapse.
Keywords: Hippocampal mossy fiber synapses; short-term potentiation; long-term potentiation; presynaptic plasticity; electron microscopy; freeze-fracture replica labeling; paired recordings; forskolin; cyclic adenosine monophosphate (cAMP); protein kinase A (PKA); neuromodulation; synaptic vesicle pools; presynaptic Ca2+ channels; Munc13; docking; priming; active zone

Filling the holes of non-manifold self-intersecting meshes for implicit topology changes in surface tracking - Etemadihaghighi, Arian
Physics simulation in computer graphics can bring triangle meshes into topologically invalid states. The method in this thesis contributed to Heiss-Synak* and Kalinov* et al. [2024] who devised a non-manifold hybrid surface tracker—a surface tracker that repairs explicit non-manifold triangle meshes with the help of the implicit domain. Specifically, this thesis provides an algorithm for filling the holes that are left after removing problematic parts of the mesh.
Keywords: surface tracking; non-manifold; hole-filling; topology change; multi-material; solid-modeling

Molecular and cellular mechanisms of motor circuit development - Kratsios, Paschalis; Zampieri, Niccolò; Carrillo, Robert; Mizumoto, Kota; Sweeney, Lora Beatrice Jaeger; Philippidou, Polyxeni (The Journal of Neuroscience)
Motor circuits represent the main output of the central nervous system and produce dynamic behaviors ranging from relatively simple rhythmic activities like swimming in fish and breathing in mammals to highly sophisticated dexterous movements in humans. Despite decades of research, the development and function of motor circuits remain poorly understood. Breakthroughs in the field recently provided new tools and tractable model systems that set the stage to discover the molecular mechanisms and circuit logic underlying motor control. Here, we describe recent advances from both vertebrate (mouse, frog) and invertebrate (nematode, fruit fly) systems on cellular and molecular mechanisms that enable motor circuits to develop and function and highlight conserved and divergent mechanisms necessary for motor circuit development.

Redshifted sodium transient near exoplanet transit - Oza, Apurva V.; Seidel, Julia V.; Hoeijmakers, H. Jens; Unni, Athira; Kesseli, Aurora Y.; Schmidt, Carl A.; Sivarani, Thirupathi; Bello-Arufe, Aaron; Gebek, Andrea; Meyer Zu Westram, Moritz; Sousa, Sérgio G.; Lopes, Rosaly M.C.; et al. (Astrophysical Journal Letters)
Neutral sodium (Na i) is an alkali metal with a favorable absorption cross section such that tenuous gases are easily illuminated at select transiting exoplanet systems. We examine both the time-averaged and time-series alkali spectral flux individually, over 4 nights at a hot Saturn system on a ∼2.8 day orbit about a Sun-like star WASP-49 A. Very Large Telescope/ESPRESSO observations are analyzed, providing new constraints. We recover the previously confirmed residual sodium flux uniquely when averaged, whereas night-to-night Na i varies by more than an order of magnitude. On HARPS/3.6 m Epoch II, we report a Doppler redshift at vΓ,NaD = + 9.7 ± 1.6 km s−1 with respect to the planet's rest frame. Upon examining the lightcurves, we confirm night-to-night variability, on the order of ∼1%–4% in NaD, rarely coinciding with exoplanet transit, not readily explained by stellar activity, starspots, tellurics, or the interstellar medium. Coincident with the ∼+10 km s−1 Doppler redshift, we detect a transient sodium absorption event dFNaD/F⋆ = 3.6% ± 1% at a relative difference of ΔFNaD(t) ∼ 4.4% ± 1%, lasting ΔtNaD ≳ 40 minutes. Since exoplanetary alkali signatures are blueshifted due to the natural vector of radiation pressure, estimated here at roughly ∼−5.7 km s−1, the radial velocity is rather at +15.4 km s−1, far larger than any known exoplanet system. Given that the redshift magnitude vΓ is in between the Roche limit and dynamically stable satellite orbits, the transient sodium may be a putative indication of a natural satellite orbiting WASP-49 A b.

Complex vaccination strategies prevent the emergence of vaccine resistance - Rella, Simon; Kulikova, Yuliya A.; Minnegalieva, Aygul; Kondrashov, Fyodor (Evolution: International journal of organic evolution)
Vaccination is the most effective tool to control infectious diseases. However, the evolution of vaccine resistance, exemplified by vaccine resistance in SARS-CoV-2, remains a concern. Here, we model complex vaccination strategies against a pathogen with multiple epitopes—molecules targeted by the vaccine. We found that a vaccine targeting one epitope was ineffective in preventing vaccine escape. Vaccine resistance in highly infectious pathogens was prevented by the full-epitope vaccine, that is, one targeting all available epitopes, but only when the rate of pathogen evolution was low. Strikingly, a bet-hedging strategy of random administration of vaccines targeting different epitopes was the most effective in preventing vaccine resistance in pathogens with the low rate of infection and high rate of evolution. Thus, complex vaccination strategies, when biologically feasible, may be preferable to the currently used single-vaccine approaches for long-term control of disease outbreaks, especially when applied to livestock with near 100% vaccination rates.

Fully dynamic k-means coreset in near-optimal update time - La Tour, Max Dupré; Henzinger, Monika H; Saulpic, David (32nd Annual European Symposium on Algorithms)
We study in this paper the problem of maintaining a solution to k-median and k-means clustering in a fully dynamic setting. To do so, we present an algorithm to efficiently maintain a coreset, a compressed version of the dataset, that allows easy computation of a clustering solution at query time. Our coreset algorithm has near-optimal update time of Õ(k) in general metric spaces, which reduces to Õ(d) in the Euclidean space ℝ^d. The query time is O(k²) in general metrics, and O(kd) in ℝ^d. To maintain a constant-factor approximation for k-median and k-means clustering in Euclidean space, this directly leads to an algorithm with update time Õ(d), and query time Õ(kd + k²). To maintain a O(polylog k)-approximation, the query time is reduced to Õ(kd).

Connectivity oracles for predictable vertex failures - Hu, Bingbing; Kosinas, Evangelos; Polak, Adam (32nd Annual European Symposium on Algorithms)
The problem of designing connectivity oracles supporting vertex failures is one of the basic data structures problems for undirected graphs. It is already well understood: previous works [Duan-Pettie STOC'10; Long-Saranurak FOCS'22] achieve query time linear in the number of failed vertices, and it is conditionally optimal as long as we require preprocessing time polynomial in the size of the graph and update time polynomial in the number of failed vertices. We revisit this problem in the paradigm of algorithms with predictions: we ask if the query time can be improved if the set of failed vertices can be predicted beforehand up to a small number of errors. More specifically, we design a data structure that, given a graph G = (V,E) and a set of vertices predicted to fail D̂ ⊆ V of size d = |D̂|, preprocesses it in time Õ(d|E|) and then can receive an update given as the symmetric difference between the predicted and the actual set of failed vertices D̂△D = (D̂ ⧵ D) ∪ (D ⧵ D̂) of size η = |D̂△D|, process it in time Õ(η⁴), and after that answer connectivity queries in G ⧵ D in time O(η). Viewed from another perspective, our data structure provides an improvement over the state of the art for the fully dynamic subgraph connectivity problem in the sensitivity setting [Henzinger-Neumann ESA'16]. We argue that the preprocessing time and query time of our data structure are conditionally optimal under standard fine-grained complexity assumptions.

Introducing the COST action ‘Improving the Quality of Biomedical Science with 3Rs Concepts’ (IMPROVE) - Kitsara, Maria; Smajlhodžić-Deljo, Merima; Gurbeta Pokvic, Lejla; Bert, Bettina; Bubalo, Nataliia; Erden, Sevilay; Franco, Nuno Henrique; Chirico, Giuseppe; Gómez Raja, Jonathan; Gonzalez-Uarquin, Fernando; Lang, Annemarie; Linklater, Nicole; et al. (Alternatives to Laboratory Animals)

Feeling the danger: Local wound signaling in plants - Hörmayer, Lukas; Friml, Jiří (Cell Research)
Local wound signaling in plants informs the surrounding tissues about an injury and initiates the regeneration process. In a recent paper published in Cell, Yang and colleagues show the involvement of a single Pep family member from tomato in wound signaling and how exogenous application of this regeneration factor enhances transformation efficiency in crops.

T-dual branes on hyperkähler manifolds - Sisak, Maria A
In [KW06] Kapustin and Witten conjectured that there is a mirror symmetry relation between the hyperkähler structures on certain Higgs bundle moduli spaces. As a consequence, they conjecture an equivalence between categories of BBB and BAA-branes. At the classical level, this mirror symmetry is given by T-duality between semi-flat hyperkähler structures on algebraic integrable systems. In this thesis, we investigate the T-duality relation between hyperkähler structures and the corresponding branes on affine torus bundles. We use the techniques of generalized geometry to show that semi-flat hyperkähler structures are T-dual on algebraic integrable systems. We also describe T-duality for generalized branes. Motivated by Fourier-Mukai transform we upgrade the T-duality between generalized branes to T-duality of submanifolds endowed with U(1)-bundles and connections. This T-duality in the appropriate context specializes to T-duality between BBB and BAA-branes.
Keywords: hyperkaehler geometry; branes; mirror symmetry; T-duality

Bilateral interactions of optic-flow sensitive neurons coordinate course control in flies - Pokusaeva, Victoria; Satapathy, Roshan K; Symonova, Olga; Jösch, Maximilian A (Nature Communications)
Animals rely on compensatory actions to maintain stability and navigate their environment efficiently. These actions depend on global visual motion cues known as optic-flow. While the optomotor response has been the traditional focus for studying optic-flow compensation in insects, its simplicity has been insufficient to determine the role of the intricate optic-flow processing network involved in visual course control. Here, we reveal a series of course control behaviours in Drosophila and link them to specific neural circuits. We show that bilateral electrical coupling of optic-flow-sensitive neurons in the fly’s lobula plate are required for a proper course control. This electrical interaction works alongside chemical synapses within the HS-H2 network to control the dynamics and direction of turning behaviours. Our findings reveal how insects use bilateral motion cues for navigation, assigning a new functional significance to the HS-H2 network and suggesting a previously unknown role for gap junctions in non-linear operations.

Concerted transcriptional regulation of the morphogenesis of hypothalamic neurons by ONECUT3 - Zupančič, Maja; Keimpema, Erik; Tretiakov, Evgenii O.; Eder, Stephanie J.; Lev, Itamar; Englmaier, Lukas; Bhandari, Pradeep; Fietz, Simone A.; Härtig, Wolfgang; Renaux, Estelle; Villunger, Andreas; Hökfelt, Tomas; et al. (Nature Communications)
Acquisition of specialized cellular features is controlled by the ordered expression of transcription factors (TFs) along differentiation trajectories. Here, we find a member of the Onecut TF family, ONECUT3, expressed in postmitotic neurons that leave their Ascl1+/Onecut1/2+ proliferative domain in the vertebrate hypothalamus to instruct neuronal differentiation. We combined single-cell RNA-seq and gain-of-function experiments for gene network reconstruction to show that ONECUT3 affects the polarization and morphogenesis of both hypothalamic GABA-derived dopamine and thyrotropin-releasing hormone (TRH)+ glutamate neurons through neuron navigator-2 (NAV2). In vivo, siRNA-mediated knockdown of ONECUT3 in neonatal mice reduced NAV2 mRNA, as well as neurite complexity in Onecut3-containing neurons, while genetic deletion of Onecut3/ceh-48 in C. elegans impaired neurocircuit wiring, and sensory discrimination-based behaviors. Thus, ONECUT3, conserved across neuronal subtypes and many species, underpins the polarization and morphological plasticity of phenotypically distinct neurons that descend from a common pool of Ascl1+ progenitors in the hypothalamus.

Temporal variability and cell mechanics control robustness in mammalian embryogenesis - Fabrèges, Dimitri; Corominas-Murtra, Bernat; Moghe, Prachiti; Kickuth, Alison; Ichikawa, Takafumi; Iwatani, Chizuru; Tsukiyama, Tomoyuki; Daniel, Nathalie; Gering, Julie; Stokkermans, Anniek; Wolny, Adrian; Kreshuk, Anna; et al. (Science)
How living systems achieve precision in form and function despite their intrinsic stochasticity is a fundamental yet ongoing question in biology. We generated morphomaps of preimplantation embryogenesis in mouse, rabbit, and monkey embryos, and these morphomaps revealed that although blastomere divisions desynchronized passively, 8-cell embryos converged toward robust three-dimensional shapes. Using topological analysis and genetic perturbations, we found that embryos progressively changed their cellular connectivity to a preferred topology, which could be predicted by a physical model in which actomyosin contractility and noise facilitate topological transitions, lowering surface energy. This mechanism favored regular embryo packing and promoted a higher number of inner cells in the 16-cell embryo. Synchronized division reduced embryo packing and generated substantially more misallocated cells and fewer inner-cell–mass cells. These findings suggest that stochasticity in division timing contributes to robust patterning.

A first look at spatially resolved star formation at 4.8 < z < 6.5 with JWST FRESCO NIRCam slitless spectroscopy - Matharu, Jasleen; Nelson, Erica J.; Brammer, Gabriel; Oesch, Pascal A.; Allen, Natalie; Shivaei, Irene; Naidu, Rohan P.; Chisholm, John; Covelo-Paz, Alba; Fudamoto, Yoshinobu; Giovinazzo, Emma; Herard-Demanche, Thomas; et al. (Astronomy and Astrophysics)
We present the first results on the spatial distribution of star formation in 454 star-forming galaxies just after the epoch of reionisation (4.8 < z < 6.5) using Hα emission-line maps and F444W imaging that traces the stellar continuum from the JWST FRESCO NIRCam Slitless Spectroscopy Survey. The Hα equivalent width profiles of star-forming galaxies across the main sequence at z ∼ 5.3 with stellar masses 6.8≤ log(M*/M⊙) < 11.1 increase with radius, which provides direct evidence for the inside-out growth of star-forming galaxies just after the epoch of reionisation. GALFIT was used to calculate half-light radii, Reff, and central surface densities within 1 kiloparsec, Σ1kpc of Hα and the continuum. At a fixed stellar mass of Log(M*/M⊙) = 9.5, Σ1kpc, Hα is 1.04 ± 0.05 times higher than Σ1kpc, C, Reff, Hα is 1.18 ± 0.03 times larger than Reff, C and both Reff measurements are smaller than 1 kiloparsec. These measurements suggest the rapid build-up of compact bulges via star formation just after the epoch of reionisation. By comparison to analogous work done at lower redshifts with Hubble Space Telescope WFC3 slitless spectroscopy as part of the 3D-HST (z ∼ 1) and CLEAR (z ∼ 0.5) surveys, we find that Reff(z) evolves at the same pace for Hα and the continuum, but Σ1kpc(z) evolves faster for Hα than the stellar continuum. As a function of the Hubble parameter, Reff, Hα/Reff,C = 1.1h(z) and Σ1 kpc, Hα/Σ1 kpc,C = h(z)1.3. These parametrisations suggest that the inside-out growth of the disk starts to dominate the inside-out growth of the bulge towards lower redshifts. This is supported by the redshift evolution in the EW(Hα) profiles from FRESCO, 3D-HST, and CLEAR at fixed stellar mass and when star-forming progenitors are traced, in which in EW(Hα) rapidly increases with radius within the half-light radius at z ∼ 5.3, but EW(Hα) increases only significantly with radius in the outer disk at z ∼ 0.5.

A new census of dust and polycyclic aromatic hydrocarbons at z = 0.7-2 with JWST MIRI - Shivaei, Irene; Alberts, Stacey; Florian, Michael; Rieke, George; Wuyts, Stijn; Bodansky, Sarah; Bunker, Andrew J.; Cameron, Alex J.; Curti, Mirko; Da'Eugenio, Francesco; Dudzevičiūte, Ugne; Ji, Zhiyuan; et al. (Astronomy and Astrophysics)
Aims. This paper utilises the James Webb Space Telescope (JWST) Mid-Infrared Instrument (MIRI) to extend the observational studies of dust and polycyclic aromatic hydrocarbon (PAH) emission to a new mass and star formation rate (SFR) parameter space beyond our local Universe. The combination of fully sampled spectral energy distributions (SEDs) with multiple mid-infrared (mid-IR) bands and the unprecedented sensitivity of MIRI allows us to investigate dust obscuration and PAH behaviour from z = 0.7 up to z = 2 in typical main-sequence galaxies. Our focus is on constraining the evolution of PAH strength and the dust-obscured luminosity fraction before and during cosmic noon, the epoch of peak star formation activity in the Universe. Methods. In this study, we utilise MIRI multi-band imaging data from the SMILES survey (5 to 25 μm), complemented with NIRCam photometry from the JADES survey (1 to 5 μm), available HST photometry (0.4 to 0.9 μm), and spectroscopic redshifts from the FRESCO and JADES surveys in GOODS-S for 443 star-forming (without dominant active galactic nucleus (AGN)) galaxies at z = 0.7 − 2.0. This redshift range was chosen to ensure that the MIRI data cover mid-IR dust emission. Our methodology involved employing ultraviolet (UV) to IR energy balance SED fitting to robustly constrain the fraction of dust mass in PAHs and dust-obscured luminosity. Additionally, we inferred dust sizes from MIRI 15 μm imaging data, enhancing our understanding of the physical characteristics of dust within these galaxies. Results. We find a strong correlation between the fraction of dust in PAHs (PAH fraction, qPAH) with stellar mass. Moreover, the sub-sample with robust qPAH measurements (N = 216) shows a similar behaviour between qPAH and gas-phase metallicity to that at z ∼ 0, suggesting a universal relation: qPAH is constant (∼3.4%) above a metallicity of Z ∼ 0.5 Z⊙ and decreases to < 1% at metallicities ≲0.3 Z⊙. This indicates that metallicity is a good indicator of the interstellar medium properties that affect the balance between the formation and destruction of PAHs. The lack of a redshift evolution from z ∼ 0 − 2 also implies that above Z ∼ 0.5 Z⊙ the PAH emission effectively traces obscured luminosity and the previous locally calibrated PAH-SFR calibrations remain applicable in this metallicity regime. We observe a strong correlation between the obscured UV luminosity fraction (ratio of obscured to total luminosity) and stellar mass. Above the stellar mass of M* > 5 × 109 M⊙, on average, more than half of the emitted luminosity is obscured, while there exists a non-negligible population of lower-mass galaxies with > 50% obscured fractions. At a fixed mass, the obscured fraction correlates with SFR surface density. This is a result of higher dust covering fractions in galaxies with more compact star-forming regions. Similarly, galaxies with high IRX (IR to UV luminosity) at a given mass or UV continuum slope (β) tend to have higher ΣSFR and shallower attenuation curves, owing to their higher effective dust optical depths and more compact star-forming regions.

Portable Raman platform for SERS droplets microfludics - Quintero, Sergio; Relvas, Maria; Aranda, Marta; Nodal, Fernando; Dieguez, Lorena; Abalde-Cela, Sara (2024 International Conference on Optical MEMS and Nanophotonics)
In this work we present the engineering of a portable platform for sensing SERS signals in droplets microfluidics. This system comprised not only the read-out platform but also a design for the microfluidic devices optimized to enhanced the obtained SERS signals.

Protein cage directed assembly of binary nanoparticle superlattices - Zhou, Yu; Shaukat, Ahmed; Seitsonen, Jani; Rigoni, Carlo; Timonen, Jaakko V.I.; Kostiainen, Mauri A. (Advanced Science)
Inorganic nanoparticles can be assembled into superlattices with unique optical and magnetic properties arising from collective behavior. Protein cages can be utilized to guide this assembly by encapsulating nanoparticles and promoting their assembly into ordered structures. However, creating ordered multi-component structures with different protein cage types and sizes remains a challenge. Here, the co-crystallization of two different protein cages (cowpea chlorotic mottle virus and ferritin) characterized by opposing surface charges and unequal diameter is shown. Precise tuning of the electrostatic attraction between the cages enabled the preparation of binary crystals with dimensions up to several tens of micrometers. Additionally, binary metal nanoparticle superlattices are achieved by loading gold and iron oxide nanoparticles inside the cavities of the protein cages. The resulting structure adopts an AB2FCC configuration that also impacts the dipolar coupling between the particles and hence the optical properties of the crystals, providing key insight for the future preparation of plasmonic and magnetic nanoparticle metamaterials.

Response matching for generating materials and molecules - Cheng, Bingqing (Journal of Chemical Theory and Computation)
Diffusion models have recently emerged as powerful tools for the generation of new molecular and material structures. The key insight is that the noise in these models is related to the response of the atoms to displacement, and the denoising step is thus analogous to the geometry relaxation of atomistic systems starting from a random structure. Building on this, we present a generative method called Response Matching (RM), which leverages the fact that each stable material or molecule exists at the minimum of its potential energy surface. Any perturbation induces a response in energy and stress, driving the structure back to equilibrium. Matching this response is closely related to score matching in diffusion models. Another important aspect of state-of-the-art diffusion models is the incorporation of physical symmetries such as translation, rotation, and periodicity. RM employs a machine learning interatomic potential and random structure search as the denoising model, inherently respecting these symmetries and exploiting the locality of atomic interactions. RM handles both molecules and bulk materials under the same framework. Its efficiency and generalization are demonstrated on three systems: a small organic molecular data set, stable crystals from the Materials Project, and one-shot learning on a single diamond configuration.

Transport properties of canonical PIN-FORMED proteins from Arabidopsis and the role of the loop domain in auxin transport - Janacek, DP; Kolb, M; Schulz, L; Mergner, J; Kuster, B; Glanc, Matous; Friml, Jiří; Ten Tusscher, K; Schwechheimer, C; Hammes, UZ (Developmental Cell)
The phytohormone auxin is polarly transported in plants by PIN-FORMED (PIN) transporters and controls virtually all growth and developmental processes. Canonical PINs possess a long, largely disordered cytosolic loop. Auxin transport by canonical PINs is activated by loop phosphorylation by certain kinases. The structure of the PIN transmembrane domains was recently determined, their transport properties remained poorly characterized, and the role of the loop in the transport process was unclear. Here, we determined the quantitative kinetic parameters of auxin transport mediated by Arabidopsis PINs to mathematically model auxin distribution in roots and to test these predictions in vivo. Using chimeras between transmembrane and loop domains of different PINs, we demonstrate a strong correlation between transport parameters and physiological output, indicating that the loop domain is not only required to activate PIN-mediated auxin transport, but it has an additional role in the transport process by a currently unknown mechanism.